INDONESIAN ACCOUNTING STUDENTS’ SELF-CONFIDENCE TO ADOPT ARTIFICIAL INTELLIGENCE (AI) - Andani, Gina; Lindrianasari, Lindrianasari; Oktavia, Reni; Septiyanti, Ratna (Jurnal Akuntansi dan Keuangan Indonesia, 2022)
The development of artificial intelligence (AI) in accounting as the impact of industrial revolution 4.0 has raised various concerns regarding the future of accountants and the possibility that accountants will be replaced by AI. Businesses are continuously adopting AI globally and particularly in Indonesia, AI adoption raises concerns that accountants will be replaced with AI due to the lack of competence to work with AI. A descriptive study with a quantitative approach was conducted in January 2021 by distributing questionnaires that collected a convenience sample of 476 respondents from universities across Indonesia. The required criteria of respondents are the active Indonesian undergraduate accounting students (class of 2016-2020). Therefore, this research will examine how the AI-based curriculum provided by universities relates to the competency of prospective accountants. The research also examines how the prospective accountants’ competency affects the readiness of accounting students to adapt and work with AI so that their roles are not entirely replaced by AI, especially for Indonesian accounting students as prospective accountants. The last part of this research will underline that the development of AI therefore should not be a concern for the future of accountants and accounting students in Indonesia. However, to have the prospective accountants prepared to work with AI and enter the industry 4.0 workforce after they graduate, the accounting students need to enhance their competencies. The accounting educators also need to enhance their curricula by providing more practice-related courses to improve the capability of accounting students to operate accounting softwares.